A method for the near real-time production of quasi-definitive magnetic observatory data - Clarke, Ellen; Baillie, Orsi; J. Reay, Sarah; Turbitt, Chris W. (Earth, planets, and space, 2013)
Magnetic observatory data are widely used in the derivation of time-varying magnetic field models, often in combination with satellite magnetic data, when available. Traditionally the definitive observatory results are used, the availability of which can often lag those of the satellite data by months and even years. The recently defined quasi-definitive observatory data type has been introduced to meet the need to provide observatory data suitable for use in field modeling in a more rapid time frame and for producing Level 2 products planned for the upcoming European Space Agency Swarm mission. A method for producing quasi-definitive data is presented and the essential steps described. To evaluate the method, provisional data published on a next day basis since 2000 are tested against definitive data at five INTERMAGNET observatories. The means and standard deviations of the differences between the candidate quasi-definitive and definitive data are within the accuracy of 5 nT set by INTERMAGNET. Since the tested data were published on-line on a next day basis, they also easily meet the INTERMAGNET requirement of availability within three months. These results demonstrate that prompt production of quasi-definitive data is possible for observatories that already perform to the standards set by INTERMAGNET.